MEMBANGUN LITERASI MEMBACA PADA ANAK MELALUI METODE MEMBACA NYARING (READ ALOUD) - Eggy Rokhmatulloh1; Eyus Sudihartinih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to obtain a description of the results of a literature review to build reading literacy in children through the read aloud method. This study is important in order to obtain an overview of how to grow reading literacy. The technique of this research is literature review. Through literature, the technique of reading books aloud is obtained by parents at home and teachers at school. Emotional closeness and comfortable atmosphere when parents and teachers read books create feelings of satisfaction in children. The children in question are grade 1 to grade 3 elementary school students, with an age range of 7 to 9 years, whose way of thinking is at the concrete operational stage. Children get the expected information from reading books as well as a sense of comfort when being read to, so that children will repeat the same experience when they need information. Ask parents and teachers to read the books they want if they can't read independently or find the information they want by reading books independently. Habits that are formed, the result of repeated experiences and the satisfaction obtained by children, create children who have high reading interest.